Desenvolvimento de dois géis para a mucosa bucal de pacientes internados sob ventilação mecânica: análise in vitro das atividades antimicrobiana, hidratante e da citotoxicidade - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2018)
Infections Related to Healthcare Assistance are considered the main causes of morbidity and mortality in the hospital setting, especially in Intensive Care Units. One of the most common infections affecting patients undergoing mechanical ventilation per orotracheal intubation is ventilator-associated pneumonia. This infection presents a great relation with the altered oral microbiota. In addition, such patients usually present hyposalivation, with intense mucosa dryness, fissures and traumatic mouth lesions. Thus, the objective of this research was to develop two gels with antimicrobial activity (a 0.12% chlorhexidine digluconate gel and a 0.03% triclosan gel) associated with a moisturizing agent (d-panthenol) to be applied in the mucosa of patients admitted to the Intensive Care Unit. The study presents an interdisciplinary character, on this account the gels were formulated and submitted to in vitro tests, integrating knowledge in the areas of dentistry, pharmacy, microbiology and cytology. The characterization of each gel was carried out by the organoleptic properties (color, odor, appearance and consistency), as well as physicochemical properties (pH, density and viscosity). The antimicrobial, hydration and cytotoxicity properties were also verified. The results of the characterization tests showed that the gels had organoleptic characteristics, pH, density and viscosity ideal for use in the oral mucosa of hospitalized patients. In the antimicrobial activity, all the strains tested were sensitive to the use of the gel containing 0.12% chlorhexidine digluconate with better values when compared to the available commercial chlorhexidine mouthwash. Regarding the gel of 0.03% triclosan, the antimicrobial action was also superior when compared to the oral rinse containing 0.03% triclosan. In addition, triclosan gel was considered a non-cytotoxic and moisturizing product for oral mucosa. On the other hand, the gel of 0.11% chlorhexidine digluconate was cytotoxic and showed no moisturizing properties. In general, the two gels demonstrated that they can be used to control the oral microbiota of inpatients, as well as the triclosan gel can hydrate the oral mucosa, offering greater comfort to the hospitalized patient.
Development of two gels for the oral mucosa of patients hospitalized under mechanical ventilation: in vitro analysis of antimicrobial, moisturizing and cytotoxicity activities
Keywords: Infecção hospitalar; Clorexidina; Triclosan; Higiene bucal; Tecnologia farmacêutica; Cross infection; Chlorhexidine; Triclosan; Oral hygiene; Technology; Pharmaceutical; CNPQ::CIENCIAS DA SAUDE